2017
DOI: 10.1038/s41598-017-09143-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of brown planthopper-responsive microRNAs in resistant and susceptible rice plants

Abstract: The brown planthopper (BPH) is the most devastating insect pest of rice. The rice gene BPH15 confers resistance to BPH. MicroRNAs (miRNAs) regulate a spectrum of development and defense response processes in plants. In this study, we analyzed six miRNA profiles of a BPH15 introgression line (P15) and a susceptible recipient line (PC) at three time points (0 h, 6 h and 48 h) after BPH attack, and identified 464 known miRNAs and 183 potential novel miRNAs. Before the BPH feeding, we identified 23 miRNAs differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 69 publications
2
49
1
Order By: Relevance
“…Seventeen of the miR-NAs, miR160c-3p/e-3p, miR166a-5p/e-5p/h-5p, miR169h/i-5p.1/i-5p.2/j/k/l, miR1859, miR1861b/j/l, miR390-3p and miR396c-3p, were present in both groups, suggesting their involvement in the defense response of rice against BPH are consistent with their respective roles in pathogen defense [24][25][26]. Previously, the BPH-responsive miRNAs were identified in a BPH15 introgression line [29]. In both the BPH15 introgression and the BPH6G lines, some miRNA exhibited similar expression trends, such as miR156b-3p, miR169h/i-3p/i-5p.1/i-5p.2/j/k/l/m/o, miR396c-5p, miR399j, miR530-5p and miR5513, suggesting a conserved and diverse resistance mechanisms against BPH mediated by BPH6 and BPH15.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Seventeen of the miR-NAs, miR160c-3p/e-3p, miR166a-5p/e-5p/h-5p, miR169h/i-5p.1/i-5p.2/j/k/l, miR1859, miR1861b/j/l, miR390-3p and miR396c-3p, were present in both groups, suggesting their involvement in the defense response of rice against BPH are consistent with their respective roles in pathogen defense [24][25][26]. Previously, the BPH-responsive miRNAs were identified in a BPH15 introgression line [29]. In both the BPH15 introgression and the BPH6G lines, some miRNA exhibited similar expression trends, such as miR156b-3p, miR169h/i-3p/i-5p.1/i-5p.2/j/k/l/m/o, miR396c-5p, miR399j, miR530-5p and miR5513, suggesting a conserved and diverse resistance mechanisms against BPH mediated by BPH6 and BPH15.…”
Section: Discussionsupporting
confidence: 57%
“…2a), many of which belonged to known miRNA families including miR156, miRNA160, miR166, miR169, miR1846, miR1861 and miR319 (Additional file 3: Table S2). Members of the miRNA families were reported to be involved not only in growth, development, grain size and hormone signaling, but also in response to biotic and abiotic stress [21][22][23][24][25][26][27][28][29][30][31]. These BPH6 responsive DEMs might be involved in response to BPH.…”
Section: Identification Of Mirnas Related To Bph Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…This corroborates the work of Wu et al . (Wu et al ., 2017b), which showed that many miRNAs responded differentially to BPH in resistant and susceptible rice plants, indicating that miRNAs might mediate different pathways involved in the basal defence and specific resistance to BPH. We further revealed a detailed molecular mechanism mediated by one of the responsive miRNAs, OsmiR396, which was induced by BPH infestation (Figure a,b).…”
Section: Discussionmentioning
confidence: 99%